Three-dimensional face stability analysis of rock tunnels excavated in Hoek-Brown media with a novel multi-cone mechanism. (February 2023) - Zhong, Junhao; Hou, Chuantan; Yang, Xiaoli
Abstract: In order to give a more accurate prediction of the required face pressure, this work revisits the three-dimensional (3D) face stability problems of rock tunnels excavated in Hoek-Brown media. The Piecewise Linear Method (PLM) is introduced to account for the nonlinearity of the rock strength rather than the simple linear substitution for the strength envelope. A novel multi-cone rotational mechanism consisting of n truncated curvilinear cones is generated respecting the plastic normality flow rule. Two typical linearized measures: Generalized Tangential Technique (GTT) and Equivalent Mohr-Coulomb parameters Method (EMM) are also included in this study for comparison and analysis. In terms of the energy-work balance equation, the required face pressure is formulated as an optimization problem depending on 2 n variables and is resolved by a recently-proposed Marine Predators Algorithm (MPA). Parametric study implies that the solution of two-dimensional (2D) analysis is very conservative, despite being safe in engineering, it is uneconomical compared with 3D analysis. In 3D analysis, the required face pressure predicted by PLM is significantly improved by 9 % compared with that of GTT, and the results calculated from EMM show a good consistency with PLM and GTT for heavily fractured rock mass, while for high-quality rock masses, the diversity between the results of EMM and other two methods is distinct. To further extend the application of such modified mechanism, design charts of the normalized face pressure are calculated for a quick assessment of face stability in rock masses with different quality.